Community Based Tourism Management in Bajandik Riam Tourism, Batu Benawa, Hulu Sungai Central District - Raditia, Raditia; Arbain, Taufik; Syafari, Muhammad Riduansyah (Universitas Airlangga, 2023)
This study aims to analyze and identify Community-Based Tourism Management in Riam Bajandik Tourism and examine the actors involved in managing the tourism both internally and externally. In addition to knowing the factors that influence the management of Riam Bajandik tourism. The results of the study show that tourism management is only formed based on deliberation meetings from the agreement of the residents, the management has support from the Regional Government even though in its implementation there are rules that are violated especially there is no legality nor is there a written letter, Actor involvement is only carried out by the surrounding community, namely the Village Head , Community Patrons, Religious Leaders, Pokdarwis Members and Tourism Managers. One of the principles in tourism development is that it leads to the concept of community empowerment and social participation, in which the tourism manager is only managed by the surrounding community and the spirit of mutual cooperation is high. Several inhibiting factors related to the management of Riam Bajandik Tourism, namely, frequent miscoordination and communication between managers, lack of budget for development, lack of human resources (HR) regarding Art Of Tourism (Art in Tourism), lobbying which is always accommodated by the government, and conflicts of interest in tourism business competition. Keywords: Tourism Management, Community Empowerment, Participation